2023
DOI: 10.3390/ijms24129978
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs and Adipogenesis

Abstract: Adipogenesis is regarded as an intricate network in which multiple transcription factors and signal pathways are involved. Recently, big efforts have focused on understanding the epigenetic mechanisms and their involvement in the regulation of adipocyte development. Multiple studies investigating the regulatory role of non-coding RNAs (ncRNAs) in adipogenesis have been reported so far, especially lncRNA, miRNA, and circRNA. They regulate gene expression at multiple levels through interactions with proteins, DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 125 publications
0
1
0
Order By: Relevance
“…lncRNAs are important regulatory molecules and actively participate in various biological processes [ 53 , 54 , 55 , 56 ]. The role of lncRNAs in chicken adipocyte differentiation has also attracted the attention of researchers [ 57 , 58 ]. In order to understand the upstream regulatory mechanism of SLC22A16 , this study conducted a joint analysis with our published lncRNA sequencing data and found a positive correlation between LNC6302 and SLC22A16 expression during chicken adipocyte differentiation [ 7 ], with LNC6302 being located adjacent to SLC22A16 .…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are important regulatory molecules and actively participate in various biological processes [ 53 , 54 , 55 , 56 ]. The role of lncRNAs in chicken adipocyte differentiation has also attracted the attention of researchers [ 57 , 58 ]. In order to understand the upstream regulatory mechanism of SLC22A16 , this study conducted a joint analysis with our published lncRNA sequencing data and found a positive correlation between LNC6302 and SLC22A16 expression during chicken adipocyte differentiation [ 7 ], with LNC6302 being located adjacent to SLC22A16 .…”
Section: Discussionmentioning
confidence: 99%